2016
DOI: 10.3390/educsci6040033
|View full text |Cite
|
Sign up to set email alerts
|

Toward Culturally Sustaining Leadership: Innovation beyond ‘School Improvement’ Promoting Equity in Diverse Contexts

Abstract: Whilst school principals and educational leaders are increasingly constrained by standardized assessment results and student achievement, persistent achievement gaps continue to separate poor and historically underserved students from their wealthier mainstream peers in the United States (US) and similar countries. Unprecedented levels of cultural, linguistic, ethnic, racial, and gender school diversity underscore these phenomena. As a result, leadership for 'school improvement' has become the norm and as evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The curricula were infused with Indigenous history, language, culture, and artistic heritage that supported the use of traditional teaching strategies and served as vehicles for bridging Indigenous knowledge with conventional academic learning. It seemed evident that staff and faculty at FNUniv were providing what several authors (Ladson-Billings, 2014;Paris, 2012;Santamaría & Santamaría, 2016) described as culturally sustaining practices, an approach defined as having the "explicit goal [of] supporting multilingualism and multi-culturalism in practice and perspective for students and teachers" (Paris, 2012, p. 95). Paris (2012) suggested that such approaches go beyond being responsive or relevant to the cultures of minoritized youth in that they "seek to perpetuate and foster-to sustain-linguistic, literate, and cultural pluralism as part of the democratic project of schooling" (p. 95).…”
Section: Discussionmentioning
confidence: 99%
“…The curricula were infused with Indigenous history, language, culture, and artistic heritage that supported the use of traditional teaching strategies and served as vehicles for bridging Indigenous knowledge with conventional academic learning. It seemed evident that staff and faculty at FNUniv were providing what several authors (Ladson-Billings, 2014;Paris, 2012;Santamaría & Santamaría, 2016) described as culturally sustaining practices, an approach defined as having the "explicit goal [of] supporting multilingualism and multi-culturalism in practice and perspective for students and teachers" (Paris, 2012, p. 95). Paris (2012) suggested that such approaches go beyond being responsive or relevant to the cultures of minoritized youth in that they "seek to perpetuate and foster-to sustain-linguistic, literate, and cultural pluralism as part of the democratic project of schooling" (p. 95).…”
Section: Discussionmentioning
confidence: 99%
“…Yosso applies the concepts of Critical Race Theory (CRT) to shift deficit thinking placed on Communities of Color and to deconstruct how these relate to community and family engagement in schooling. Yosso’s work inspired some recent developments in the field of educational change in creating and supporting culturally sustaining leadership practices (FitzGerald & Quiñones, 2019; Santamaría & Santamaría, 2016; Santamaría, 2014) that school leaders draw on to better support their students (Lee & Walsh, 2019). This is significant because more than 1,000 transfronterizos/as students, who are U.S. citizens, cross the border daily to go to school in DPSD thus rendering this perspective necessary as it allows a more emancipatory approach to research.…”
Section: Methodsmentioning
confidence: 99%
“…Principal Howard’s yearly SIPs reflected the use of a continuous improvement model, in which she prioritized a literacy focus. Principal Howard consistently and continuously communicated a literacy vision for the school (Plaatjies, 2019); monitored the vision qualitatively and quantitatively (Crum, 2008; Houck & Novak, 2017); built consensus and collaborative partnerships among faculty, staff, students, and stakeholders (Riley & Webster, 2016; Santamaria & Santamaria, 2016); and celebrated the literacy growth of students. Undergirding these practices were a foundation of trust (Tschannen-Moran & Hoy, 2000), the ability to build capacity to support student learning in staff and families (Brazer & Bauer, 2013), and the provision of organizational structures that provided the time, spaces, and personnel required to realize the literacy vision (Danielson, 2002; Ford & Youngs, 2018).…”
Section: Case Analysis/teaching Notesmentioning
confidence: 99%
“…With an understanding of the school and community context, they work to reduce oppressive and exclusionary practices in themselves and their staff. Principal literacy leaders use their understanding of the context to form a plan that unites their knowledge of literacy content knowledge and instruction (Dowell et al, 2012; Hollenbeck & Rieckhoff, 2014; ILA, 2019; Murphy, 2004; Overholt & Szabocsik, 2013; Taylor, 2004) with their knowledge of culturally responsive and inclusive practices to reduce the reading achievement gap of marginalized students (Horsford et al, 2011; Keehne et al, 2018; Khalifa, 2018; Khalifa et al, 2016; Riley & Webster, 2016; Santamaria & Santamaria, 2016).…”
Section: The Principal As Literacy Leadermentioning
confidence: 99%
See 1 more Smart Citation